Calculati:
a) 2•(-3)•4-(-3)•(+4)
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
Explicație pas cu pas:
a)
2 × ( - 3 ) × 4 - ( - 3 ) × ( + 4 ) = - 12
- ( - 3 × 4) = - ( - 12 ) = + 12 ( -) ×(-) = +
= - 6 × 4 + 12 =
= - 24 + 12 =
= - 12
Răspuns de
0
Răspuns:
12
Explicație pas cu pas:
a) 2×(-3)=-6
4-[-3×4]=4+12=16
=> -6×4+12=-24+12=12
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă